2010
DOI: 10.1093/neuonc/noq110
|View full text |Cite
|
Sign up to set email alerts
|

Methylation profiling identifies 2 groups of gliomas according to their tumorigenesis

Abstract: Extensive genomic and gene expression studies have been performed in gliomas, but the epigenetic alterations that characterize different subtypes of gliomas remain largely unknown. Here, we analyzed the methylation patterns of 807 genes (1536 CpGs) in a series of 33 low-grade gliomas (LGGs), 36 glioblastomas (GBMs), 8 paired initial and recurrent gliomas, and 9 controls. This analysis was performed with Illumina's Golden Gate Bead methylation arrays and was correlated with clinical, histological, genomic, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
87
0
4

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 55 publications
16
87
0
4
Order By: Relevance
“…Other prognostic markers in gliomas include 1p19q LOH (27), IDH1 mutation status (6,28,29), and MGMT methylation status (3,6,28) or whole-genome approaches such as gene expression profiling (20,25,26,30) and, similar to reported in this study, methylation profiling (13)(14)(15). These prognostic markers may help classify gliomas as histologic classification is troublesome and subject to interobserver variation (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Other prognostic markers in gliomas include 1p19q LOH (27), IDH1 mutation status (6,28,29), and MGMT methylation status (3,6,28) or whole-genome approaches such as gene expression profiling (20,25,26,30) and, similar to reported in this study, methylation profiling (13)(14)(15). These prognostic markers may help classify gliomas as histologic classification is troublesome and subject to interobserver variation (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 71%
“…13). Later studies showed that histologic subtype was associated with methylation class and IDH1 mutation, and that GBMs generally show less overall CpG methylation than lower grade gliomas (14,15). Identification of CpG methylation sites in gliomas may therefore identify genes involved in the initiation and/or progression of gliomas [see e.g., (16,17)].…”
Section: Introductionmentioning
confidence: 99%
“…RBP1 has been demonstrated to be one of the genes most frequently subject to epigenetic silencing in G-CIMP+ primary GBMs (Noushmehr et al 2010;Laffaire et al 2011) and was also among the most strikingly subject to concordant hypermethylation and down-regulation in our model. In addition to gliomas, RBP1 is also silenced in conjunction with promoter hypermethylation in several cancer types, including lymphomas, esophageal squamous cell carcinomas, and gastric carcinomas (Esteller et al 2002;Mizuiri et al 2005;Shutoh et al 2005;Chu et al 2006).…”
Section: G-cimp+ As Compared With G-cimpà Proneural Gbms Andmentioning
confidence: 69%
“…A subset of primary GBMs exhibit the ''CpG island methylator phenotype'' (CIMP) and show concordant hypermethylation of a large number of CpG islands Noushmehr et al 2010). Interestingly, in gliomas, the CIMP phenotype (termed G-CIMP) has a striking association with IDH1 mutation (Noushmehr et al 2010;Christensen et al 2011;Laffaire et al 2011;Turcan et al 2012). Similarly, IDH1 and IDH2 mutations robustly associate with specific global DNA hypermethylation phenotypes in AMLs (Figueroa et al 2010a), enchondromas (Pansuriya et al 2011), and low-grade gliomas (LGGs) .…”
Section: Monoallelic Point Mutations Of the Nadpmentioning
confidence: 99%
“…10,13,14 According to this hypothesis, we focused our analysis on 3 genes frequently hypomethylated in GBM (i.e., the MMP2, SH3BP2, and Serpine1 genes) and on 9 genes frequently hypermethylated in GBM (i.e., the AHR, CD81, DIO3, FZD9, HTR1B, HCK, IRAK3, PRKCDBP, and TUSC3 genes) (Fig. 4A).…”
mentioning
confidence: 99%